A Proposed Project for an Electronic Center for Comprehensive Documentation of Sunnah: Vision and Ambition - Suleiman Abdullah AlSaud (Journal of Islamic Studies, 2014)
This research explores ideas and visions for the establishment of an electronic documentation center to serve the Sunnah promotion purposes, e.g. teaching, training and academic research. It attempts to draw a blueprint that serves competent, comprehensive academic documentation requirements by using up-to-date technologies. The research aim is to make good use of advanced computer programming for the service of the Sunnah sciences. It seeks to establish an ideal electronic model of computerized scientific comprehensive documentation of the Sunnah. The research methodology includes surveying, induction, data collection, opinion naires eliciting views of researchers in the field electronic documentation. The research concludes that the establishment of such a center concerned with electronic documentation can enhance the efficiency of specialized Sunnah departments, keeping them abreast of related advances and securing the development and production of desired reliable outcomes. The research recommends the establishment of a specialized electronic center for comprehensive academic documentation of the Sunnah and related training. The center should be a reference for evaluating and certifying related applications. It should also create a suitable atmosphere for motivating researchers and those concerned with learning high quality documentation.